Energy Dose-Response in Selective Laser Trabeculoplasty: A Review. Issue 8 (15th August 2022) - Radcliffe, Nathan; Gazzard, Gus; Samuelson, Thomas; Khaw, Peng; Sun, Xinghuai; Aung, Tin; Lam, Dennis; Singh, Kuldev; Katz, L. Jay; Aronov, Michael; Sacks, Zachary; Solberg, Yoram; et al.
Abstract : Précis: A literature review of selective laser trabeculoplasty (SLT) energy dose-response found no definitive relationship between intraocular pressure (IOP) reduction with respect to total or pulse energy, race, pigmentation, or application pattern. Purpose: SLT is a safe and effective treatment for lowering IOP. Although evidence is mounting for the advantage of its use as a first-line treatment for IOP reduction, the SLT procedures in use vary widely. The purpose of this literature review was to investigate whether there were any relationships between SLT energy and efficacy for lowering IOP in the published literature. Methods: A literature review was undertaken that included studies in which energy levels required for successful SLT treatment were investigated: in general, with respect to angle pigmentation, race or ethnicity, and treatment arc extent. Results: There was no indication that higher (or lower) energy used in the treatment leads to greater (or less) IOP reduction. Similar results were obtained regarding the level of trabecular meshwork pigmentation. Race was not found to be associated with altered dose response in SLT. There were indications that treating the full 360 degrees, as opposed to smaller arcs, could be beneficial for more IOP reduction. IOP reduction from SLT was found to be similar to that provided by topical medications. Conclusions: The optimal energy level of SLT needed for IOP reduction has not yet been definitively established, with all reported pulse energies resulting in similar IOP reduction. Furthermore, similar lack of conclusive findings exists regarding optimal SLT energy dosage for use in different races and degrees of trabecular meshwork pigmentation. This parameter and each of the abovementioned factors requires further research.